Biodiversity of epiphytic periphyton in the leaves of the seagrass bed of Talawaan Bajo Estuary, North Sulawesi, Indonesia - Nova L.I.M. Ogi; Endang Yuli Herawati; Yenny Risjani; Mohammad Mahmudi (Society for Indonesian Biodiversity, 2021)
Abstract. Ogi NLIM, Herawati EY, Risjani Y, Mahmudi M. 2021. Biodiversity of epiphytic periphyton in the leaves of the seagrass bed of Talawaan Bajo Estuary, North Sulawesi, Indonesia. Biodiversitas 22: 4857-4864. This study aimed to analyze the diversity of epiphytic periphyton on the leaves of the seagrass bed of Talawaan Bajo estuary North Sulawesi Indonesia. The study was performed in three sampling points by using the line transect method with 50x50 cm2. The sampling points were located in front of the residential area, the mangrove forest, and in budo Cape. Seagrass and periphyton communities were analyzed for species density, relative frequency, diversity, evenness, and dominance index. Water quality and heavy metal Hg were also measured. The results showed that Cymodocea rotundata was the dominant seagrass based on species density and frequency distribution. Periphyton composition on the leaf of C. rotundata consisted of Bacillariophyceae (16 genera), Cyanophyceae (3 genera), Chlorophyceae (9 genera), Dinophyceae (1 genus), and Rhodophyceae (1 genus). The water quality, such as phosphate, current, nitrate, dissolved oxygen, and Hg content in the water, contributed to changing the environmental condition of Talawaan Bajo waters. Therefore, the efforts to manage coastal resource conservation in the Talawaan Bajo estuary require more concern from the government and stakeholders of Talawaan Bajo.